β Subunits Functionally Differentiate Human Kv4.3 Potassium Channel Splice Variants - Abbott, Geoffrey W. (Frontiers in Physiology, 2017)
The human ventricular cardiomyocyte transient outward K+ current (Ito) mediates the initial phase of myocyte repolarization and its disruption is implicated in Brugada Syndrome and heart failure (HF). Human cardiac Ito is generated primarily by two Kv4.3 splice variants (Kv4.3L and Kv4.3S, diverging only by a C-terminal, S6-proximal, 19-residue stretch unique to Kv4.3L), which are differentially remodeled in HF, but considered functionally alike at baseline. Kv4.3 is regulated in human heart by β subunits including KChIP2b and KCNEs, but their effects were previously assumed to be Kv4.3 isoform-independent. Here, this assumption was tested experimentally using two-electrode voltage-clamp analysis of human subunits co-expressed in Xenopus laevis oocytes. Unexpectedly, Kv4.3L-KChIP2b channels exhibited up to 8-fold lower current augmentation, 40% slower inactivation, and 5 mV-shifted steady-state inactivation compared to Kv4.3S-KChIP2b. A synthetic peptide mimicking the 19-residue stretch diminished these differences, reinforcing the importance of this segment in mediating Kv4.3 regulation by KChIP2b. KCNE subunits induced further functional divergence, including a 7-fold increase in Kv4.3S-KCNE4-KChIP2b current compared to Kv4.3L-KCNE4-KChIP2b. The discovery of β-subunit-dependent functional divergence in human Kv4.3 splice variants suggests a C-terminal signaling hub is crucial to governing β-subunit effects upon Kv4.3, and demonstrates the potential significance of differential Kv4.3 gene-splicing and β subunit expression in myocyte physiology and pathobiology.